Web intelligence and security : advances in data and text mining techniques for detecting and preventing terrorist activities on the web - Last, Mark; Kandel, Abraham (NATO science for peace and security series. Information and communication security., 2010)
Terrorists are continuously learning to utilize the Internet as an accessible and cost-effective information infrastructure. Since a constant manual monitoring of terrorist-generated multilingual web content is not a feasible task, automated Web Intelligence and Web Mining methods are indispensable for efficiently securing the Web against its misuse by terrorists and other dangerous criminals. Web Intelligence and Security contains chapters by the key speakers of the NATO Advanced Research Workshop on Web Intelligence and Security that took place on November 18-20, 2009 in Ein-Bokek, Israel. This Workshop has brought together a multinational group of leading scientists and practitioners interested in exploiting data and text mining techniques for countering terrorist activities on the Web. Most talks were focused on presenting available methods and tools that can alleviate the information overload of intelligence and security experts. The key features of this book include: An up-to-date analysis of the current and future threats of the Internet misuse by terrorists and other malicious elements including cyberterrorism, terror financing and interactive online communication by terrorists and their supporters; Detailed presentation of the state-of-the-art algorithms and tools aimed at detecting and monitoring malicious online activities on the Web; Introduction of novel data mining and text mining methods that can be used to efficiently analyze the massive amounts of multi-lingual Web content; The book's wide audience includes research scientists, graduate students, intelligence analysts, and data / text mining practitioners.